Synthesis of DOTA-pyridine chelates for 64Cu coordination and radiolabeling of αMSH peptide - Hua Yang; Feng Gao; Brooke McNeil; Chengcheng Zhang; Zheliang Yuan; Stefan Zeisler; Joel Kumlin; Jutta Zeisler; François Bénard; Caterina Ramogida; Paul Schaffer (SpringerOpen, 2021)
Abstract Background 64Cu is one of the few radioisotopes that can be used for both imaging and therapy, enabling theranostics with identical chemical composition. Development of stable chelators is essential to harness the potential of this isotope, challenged by the presence of endogenous copper chelators. Pyridyl type chelators show good coordination ability with copper, prompting the present study of a series of chelates DOTA-xPy (x = 1-4) that sequentially substitute carboxyl moieties with pyridyl moieties on a DOTA backbone. Results We found that the presence of pyridyl groups significantly increases 64Cu labeling conversion yield, with DOTA-2Py, −3Py and -4Py quantitatively complexing 64Cu at room temperature within 5 min (1 × 10− 4 M). [64Cu]Cu-DOTA-xPy (x = 2-4) exhibited good stability in human serum up to 24 h. When challenged with 1000 eq. of NOTA, no transmetallation was observed for all three 64Cu complexes. DOTA-xPy (x = 1-3) were conjugated to a cyclized α-melanocyte-stimulating hormone (αMSH) peptide by using one of the pendant carboxyl groups as a bifunctional handle. [64Cu]Cu-DOTA-xPy-αMSH retained good serum stability (> 96% in 24 h) and showed high binding affinity (Ki = 2.1-3.7 nM) towards the melanocortin 1 receptor. Conclusion DOTA-xPy (x = 1-3) are promising chelators for 64Cu. Further in vivo evaluation is necessary to assess the full potential of these chelators as a tool to enable further theranostic radiopharmaceutical development.